Pengaruh Pemberian Cookies Tepung Hati Sapi dan Kacang Polong terhadap Kadar Hemoglobin Remaja Putri Anemia di SMA Negeri 11 Palembang - Firmansyah, Muhammad; Sadiq, Ahmad; Muzakar, Muzakar (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2024)
Anemia, defined by a hemoglobin or red blood cell count below 12 g/dl, is one of the most common forms of malnutrition globally. Foods rich in iron and folic acid may help people with anemia raise their blood hemoglobin levels. In this experiment, female students with anemia were given cookies made with beef liver flour and peas to see how their hemoglobin levels changed. The study is quasi-experimental in nature, using a control group design with pre- and post-tests. Quota sampling was employed to determine the study sample, which consisted of 25 treatment and comparison groups. The data was analyzed using paired sample t-test and dependent sample t-test. The average hemoglobin level increased from 10.38 g/dl before the intervention to 12.19 g/dl after it, according to statistical testing. The average change in hemoglobin levels between the two measurements was 1.80 g/dl. Afterwards, the statistical test yielded a p value of 0.000, which is less than 0.05. Giving beef liver cookies and peas has an impact on boosting hemoglobin levels before and after the intervention, according to this formula.